PENERAPAN METODE CERAMAH DALAM MENINGKATKAN PEMAHAMAN QAWAID PADA PEMBELAJARAN BAHASA ARAB DI MIS AL-WASHLIYAH SEI BULUH - Aslam Annashir; Azizah Sabrina Gajah; Citra Sukma Ayu (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2023)
This research aims to analyze and evaluate the impact of applying the lecture method in increasing understanding of qawaid in the Arabic language learning process at MIS Al-Washliyah Sei Buluh. The lecture method is considered an approach that can improve students' understanding of Arabic language rules. The research was carried out using a qualitative approach involving Arabic language teachers and students of MIS Al-Washliyah Sei Buluh as research subjects. Data was collected through classroom observations, interviews with teachers, and analysis of documents related to lesson material. The data collection process was carried out over a certain period to identify the impact of the lecture method on students' understanding of qawaid. The research results showed that the application of the lecture method was successful in increasing students' understanding of qawaid in learning Arabic. It was found that there was an increase in active student participation, increased interest in the lesson material, and improved overall understanding. The teacher also said that the lecture method provided a more interactive and effective learning atmosphere.